Clinician treatment choices for post-traumatic stress disorder: ambassadors survey of psychiatrists in 39 European countries - Martina Rojnic Kuzman; Frank Padberg; Benedikt L. Amann; Meryam Schouler-Ocak; Zarko Bajic; Tarja Melartin; Adrian James; Julian Beezhold; Jordi Artigue Gómez; Celso Arango; Tihana Jendricko; Jamila Ismayilov; et al. (European Psychiatry, 2024)
Abstract